2‐Nitroveratryl as a Photocleavable Thiol‐Protecting Group for Directed Disulfide Bond Formation in the Chemical Synthesis of Insulin. Issue 31 (24th June 2014) - Karas, John A.; Scanlon, Denis B.; Forbes, Briony E.; Vetter, Irina; Lewis, Richard J.; Gardiner, James; Separovic, Frances; Wade, John D.; Hossain, Mohammed A.
Abstract Chemical synthesis of peptides can allow the option of sequential formation of multiple cysteines through exploitation of judiciously chosen regioselective thiol‐protecting groups. We report the use of 2‐nitroveratryl (oNv) as a new orthogonal group that can be cleaved by photolysis under ambient conditions. In combination with complementary S‐pyridinesulfenyl activation, disulfide bonds are formed rapidly in situ. The preparation of Fmoc‐Cys(oNv)‐OH is described together with its use for the solid‐phase synthesis of complex cystine‐rich peptides, such as insulin.